Reunión de funcionarios de la UNED. (UNED, 2023)
Aparece Héctor Mejía, María Cascante Prada (ECEN), Edgar Castillo Cruz (ECEN), Jesusita Alvarado Blanco de CONCAL, Carlos Marigal Tellini (Oficina de Investigación Institucional), Virginia Espeleta Delgado (ECEN), Ana Isabel Tristán Sánchez (Procuraduría)